VD_FINDINFO Arrêt / 2024 / 690 vom 26. September 2024 - VD Tribunal cantonal (2024)
ENQUÊTEEN GÉNÉRAL, TENUE DU MÉNAGE, DOMMAGE MÉNAGER, AIASSURANCE | 28 LAI, 28a LAI, 4 al. 1 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 LPGA, 27bis RAI